TRANSLANGUAGING IN TESOL: A SYSTEMATIC REVIEW - Nabila Sakinah; Hendriwanto; Nunung Nurjannah (Cirebon International Conference on Education and Economics Proceeding, 2024)
The concept of translanguaging has gained prominence in the field of education, particularly in bilingual education, as it encourages educators to utilize students' language skills and create engaging language learning settings. In this research, the author gathered data from various reputable sources such as Taylor and Francis, ELSEVIER, Springer, Research Gate, JLLS (Journal of Language and Linguistic Studies), and TESOL quarterly. A thorough review was conducted on a total of 20 journals and books. The data suggests that there was a significant increase in the number of journal publications in 2020 compared to previous years. The results of this study suggest that the identity of the participating teachers plays a significant role in their ability to adapt to new languages and employ translanguaging techniques effectively in their classrooms. By doing so, teachers can establish a welcoming and supportive learning environment for students learning English.